Exploring fatigue in Marfan and hypermobile Ehlers-Danlos syndromes: an analytical cross-sectional study in two Italian healthcare centres - Rosario Caruso; Alessandro Pini; Gianluca Conte; Arianna Magon; Irene Baroni; Edward Callus; Nathasha Udugampolage; Jacopo Taurino; Alessandra Bassotti; Giada De Angeli; Giulia Paglione; Giuliana Trifirò (BMJ Open)
Objective This study investigates the prevalence and underlying factors of fatigue in individuals with Marfan syndrome (MFS) and hypermobile Ehlers-Danlos syndromes (hEDS), highlighting the necessity for focused research on this symptom within these patient populations.Design Cross-sectional, multicentre study.Setting Data were collected from participants diagnosed with MFS or hEDS across multiple healthcare centres.Participants The study enrolled 282 participants (127 with MFS and 155 with hEDS).Primary and secondary outcome measures Fatigue was measured using the Fatigue Severity Scale (FSS). Additional assessments included the Patient Health Questionnaire-9 (PHQ-9) for depression and the Insomnia Severity Index (ISI) for sleep disturbances.Results Participants with hEDS exhibited significantly higher median fatigue scores (FSS median=5.9, IQR=5.00–6.44) compared with the MFS group (FSS median=4.0, IQR=2.88–5.00). Significant predictors of fatigue included being female, having hEDS, participating in psychotherapy, and elevated scores on depression and insomnia scales. In the overall sample, hEDS significantly predicted fatigue (B=0.430, p=0.022), with depression and insomnia as strong influencers (PHQ-9: B=0.12, p<0.001; ISI: B=0.092, p<0.001). Notably, 80% of the hEDS group reported clinically relevant fatigue levels, compared with 31.5% in the MFS group. Daily persistence of fatigue was especially pronounced in hEDS, with 72.2% reporting everyday fatigue versus 25.2% in MFS. Temporal fatigue patterns also differed, with a more evenly distributed pattern throughout the day in hEDS, correlating with higher insomnia scores.Conclusions The results underscore the severe impact of fatigue on individuals with hEDS compared with those with MFS, suggesting the need for targeted, multidisciplinary management strategies to enhance quality of life.Trial registration number NCT05712564.